Impacts of Bermudagrass on Northern Bobwhite Chicks: Mobility and Heat Exposure - James A. Martin; Jason Burkhart; Reggie E. Thackston; John P. Carroll (National Quail Symposium Proceedings, 2017)
Conservation programs to benefit northern bobwhites (Colinus virginianus) and other agriculturally-related wildlife species often target crop-field margins for management. The Bobwhite Quail Initiative in Georgia is a program where 3- to 18-m strips are disked and left fallow for 3-year cycles. However, several exotic grasses, such as bermudagrass (Cynodon dactylon), encroach in field margins, reducing their usefulness for avian species. We hypothesized that dense mats of bermudagrass would be a physical barrier to bobwhite chicks and also serve as a heat trap reducing habitat quality. We conducted two experiments to assess these factors. First, we used human-imprinted bobwhite chicks, 5 and 10 days of age, to assess mobility through vegetation with 3 levels (none, moderate, and high) of bermudagrass invasion. There was a significant impact of bermudagrass density on mobility of 5-day old chicks (P 1⁄4 0.002), but no effect on 10-day old chicks (P 1⁄4 0.38). Second, we placed temperature recorders at ground level in plots in field margins that had .75% cover of bermudagrass and those with .75% coverage of forbs. The mean temperature of bermudagrass plots was greater than in forb plots (P 1⁄4 0.03). The percentage of time above the 40 8C critical threshold temperature for bobwhites was greatest in bermudagrass plots (P 1⁄4 0.03) and ranged over 33–38% of daytime hours, but only 6-26% for forb plots. Our data suggests that bermudagrass degrades the quality of field margins and control of exotic invasive grasses is warranted to improve their efficacy.
Keywords: bermudagrass; Colinus virginianus; Cynodon dactylon; northern bobwhites